HISTOPATHOLOGICAL CHANGES SPLEEN IN KAMPUNG CHICKEN GIVEN HERBAL MEDICINE OF ASHITABA AND AVIAN INFLUENZA VACCINE - Victoria, Velia Chyntia; Sudira, I Wayan; Winaya, Ida Bagus Oka (Buletin Veteriner Udayana, 2022)
This study aims to determine the effect of giving ashitaba leaf herbal medicine as seen from the histopathological picture of native chicken spleen vaccinated against avian influenza disease vaccine. This research uses a complete random design. The treatment consisted of five treatment groups namely without ashitaba (control), with an ashitaba dose of 50; 100; 200, and 400 mg / head were dissolved with water until the volume is 100 ml and given treatment for 14 days. On the 21st day, all groups of native chickens were vaccinated against the avian influenza vaccine. On the 42nd day, native chickens were euthanasia by cervical dislocation, then the spleen was taken to see changes in the histopathological structure. Then it continued with Hematoxylin-Eosin (HE) staining and was tested under a microscope at 400x magnification. Variables that are seen from the proliferation of lymphoid follicles on white pulp by using a scaling scale for histopathological changes. The research data were analyzed by analysis non parametric Kruskal-Wallis. The results showed that there was a significant change in spleen histopathology between treatment P0 (control) and treatment given the herbal ashitaba leaf. Giving the herbal ashitaba leaf at a dose of 400 mg/head/day improves the body defense system of native chickens vaccinated with avian influenza.